Building a Quantum Computer with Photons: Simulation Algorithm for Linear Optical Quantum Systems - Ramadian Ridho Illahi; I Wayan Sudiarta; Marzuki Marzuki; Arif Budianto; Dani Syirojulmunir (Buletin Fisika)
The evolution of quantum states on photons in linear optical systems has diverse applications, ranging from fundamental to advanced quantum optics experiments for quantum information processing. This research aims to develop a simulation algorithm that focuses on modeling optical elements as a way to study the behavior of quantum states in photons. An implementation of quantum computation with linear optics has been developed as part of the simulation in this research. The configuration of the quantum network is done by modeling optical components, such as beam splitters, phase shifters, and the relationships between their components through matrix representations. The measurement results are expressed in terms of probability distributions, taking into account the effects of the optical elements through which the photons are transmitted. The simulation is capable of performing calculations for basic quantum networks with certain initial quantum states. Through this simulation, we can define quantum networks and intuitively implement quantum algorithms using simple instructions.